Pengaruh Struktur Kepemilikan, Kinerja Keuangan, dan Ukuran Perusahaan terhadap Financial Restatement - Yulina Fransisca Nugroho; Lindrawati Lindrawati (Jurnal Akuntansi, 2021)
Financial statements contain useful information for stakeholders regarding the company’s financial condition and are used as the basis for decision making. Therefore, financial statements must prepared appropriately, high quality and reflect the actual conditions of the company so that they can be relied on for users of financial statements. Financial restatements are presented on accrual basis so it can increase manager’s flexibility in recording economic events. This flexibility can cause misstatement of information in the financial statements caused by changes in accounting required by accounting standards and indications of management fraud to act opportunistically, causing the company to undertake financial restatements. Therefore, the aim of this study is to examine and analyze the effect of ownership structure, financial performance, and company size on financial restatement. The object of research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) with the research period 2014-2018. The results showed that the ownership structure in the form of managerial ownership and institutional ownership had no effect on financial restatement, while foreign ownership had a negative effect on financial restatement. Financial performance in the form of profitability, leverage, and activities has no effect on financial restatement. Company size has a positive effect on financial restatement.